2009
DOI: 10.1111/j.1365-2842.2009.02005.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in stereognostic ability of the tongue with age

Abstract: Rehabilitation of eating and swallowing functions from the viewpoint of quality of life should attempt to restore not only the physical, but also sensory function. As the size and shape of the intra-oral bolus of food provides oral sensory information important for eating and swallowing, we investigated the stereognostic ability of the tongue in 269 young adults (mean age: 24.5 years) and 60 seniors (mean age: 80.5 years); all of whom had no eating or swallowing complaints. Assessment of the stereognostic abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…9 and 10. These results suggest that information on unique characteristics such as sharp angles or asymmetrical shapes may be useful for recognizing the shapes of test pieces, being consistent with the results of the previous study (4). This was because the subjects easily differentiated the shapes of the test pieces in each group based on unique characteristics, providing a strong input that served as clues during the tests (4,26).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…9 and 10. These results suggest that information on unique characteristics such as sharp angles or asymmetrical shapes may be useful for recognizing the shapes of test pieces, being consistent with the results of the previous study (4). This was because the subjects easily differentiated the shapes of the test pieces in each group based on unique characteristics, providing a strong input that served as clues during the tests (4,26).…”
Section: Discussionsupporting
confidence: 79%
“…Motor strategies are approaches that focus on improvement of motor function, and include the Mendelson maneuver, Masako exercise, and Shaker exercise. Motor strategies have been widely used for eating and swallowing rehabilitation in patients with stroke (3,4) because their effects on the strength of the tongue, lip pressure, and strength of the buccinators can be measured objectively through biomechanical measurements such as the Iowa Oral Performance Instrument (5). Sensory strategies are approaches that focus on improvement of sensory functions, such as thermal, mechanical, and chemical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…A probable explanation would be a difficulty in understanding the orders requested, as they are actions seldomly performed in a conscious manner by the elderly individuals evaluated in their daily routine. In addition, there is a reduction in oral stereognosis of the elderly (28) , which, in turn, may influence or be related to reduced oral motor activity (28,29) . The change in language mobility was the most important, corroborating Lima et al (9) .…”
Section: Discussionmentioning
confidence: 99%
“…The proposed experiment has been assessed by a implementing a technique which aided in identifying the shape of test pieces in the oral cavity [10,11]. In our earlier contribution we have provided information on the result of the test piece identification which were found worth investigating considering the effective outcome on oral stereognostic ability [12]. This study demonstrated that the tongue was responsible for the oral stereognostic ability and it' ability was quite high.…”
Section: Introductionmentioning
confidence: 99%
“…We advocated the immense prospect of improving the tongue's stereognostic ability in the patients through this method [12].…”
Section: Introductionmentioning
confidence: 99%